Does Person-Organization Fit (P-O Fit) Mediate the Relationship Between Employee Job Satisfaction and Turnover Intention: The Case of Insurance Agents in Malaysia - Oscar Dousin; Toh, Pei Sung; Arsiah Bahron; Iklima Husna Abdul Rahim (2020)
Turnover intention is becoming a critical issue in most organization. Employees’ are leaving their job due to an alternative job offer with an attractive salary and employment benefits,supportive supervisors and a better work environment. The study examines the relationship between job satisfaction on employee turnover intention as well as the mediating effect of person-organization (P-O) fit among insurance agents in Malaysia. The study adopts a quantitative research methodology by surveying 184 insurance agents in Sabah, Malaysia in 2019. Four hypotheses were tested with validated measures of job satisfaction (pay, supervision and communication), turnover intention and person-organization fit. The study revealed that job satisfaction (pay and supervision) has a significant and negative impact to turnover intention. In addition, job satisfaction (communication in organization) has a significant and positive impact to turnover intention. However, person-organization fit found to be not significantly mediates the relationship. The study suggested that organizations should acknowledge the importance of pay, supervision and communication in organization to improving employees’ motivation and retention in organization. The three elements of job satisfaction could improve and promote harmonious and positive work environment.